2012
DOI: 10.1016/j.nimb.2011.11.016
|View full text |Cite
|
Sign up to set email alerts
|

Electronic excitations and defect creation in wide-gap MgO and Lu3Al5O12 crystals irradiated with swift heavy ions

Abstract: A comparative study of radiation effects in two groups of single crystals with an energy gap of about 8 eV possessing drastically different lattice and electron energy structures − fcc MgO and Lu 3 Al 5 O 12 with 160 atoms per a unit cell − has been performed using crystal irradiation with vacuum ultraviolet radiation, electrons, fast fission neutrons and, in particular, ~2.2 GeV uranium ions. In MgO with the absence of self-trapping for valence holes, the localization of holes near impurity ions or bivacancie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 45 publications
3
17
0
2
Order By: Relevance
“…[39], the ratio of these reflection spectra (irradiated/virgin) contains a pronounced peak at ~7.1 eV and a small peculiarity at ~8.0 eV, that, in our opinion, confirm the formation of single and more complex (pair) LuAl defects. Our recent measurements have shown that the thermal annealing of the ~7 eV-band of SHI-induced optical absorption efficiently occurs above 1100 K (at about a half of the melting point), where the intensive ionic movement takes place already.…”
Section: Intrinsic and Impurity Antisite Defects In Lutetium Garnet Ssupporting
confidence: 65%
See 4 more Smart Citations
“…[39], the ratio of these reflection spectra (irradiated/virgin) contains a pronounced peak at ~7.1 eV and a small peculiarity at ~8.0 eV, that, in our opinion, confirm the formation of single and more complex (pair) LuAl defects. Our recent measurements have shown that the thermal annealing of the ~7 eV-band of SHI-induced optical absorption efficiently occurs above 1100 K (at about a half of the melting point), where the intensive ionic movement takes place already.…”
Section: Intrinsic and Impurity Antisite Defects In Lutetium Garnet Ssupporting
confidence: 65%
“…In SHI-irradiated LuAG, the enhancement of the emission peak amplitude was detected only at 3.254.25 eV. The absolute enhancement of this emission at ~3.75 eV of unknown origin was detected due to its short decay time (~70 ns) at 80 K [39].…”
Section: Intrinsic and Impurity Antisite Defects In Lutetium Garnet Smentioning
confidence: 89%
See 3 more Smart Citations